Między Polską piastowską a jagiellońską. Kontrowersje wokół kierunków realizacji polskiej polityki zagranicznej po akcesji do Unii Europejskiej - Mróz, Maciej (Instytut Studiów Międzynarodowych Uniwersytetu Wrocławskiego, 2013)
The admission of Poland into the Euro-Atlantic system has resulted in the strengthening of the country’s position in Europe. Thereby it has enabled the implementation of Poland’s foreign policy towards the EU member states as well as towards Ukraine, the Russian Federation and the Republic of Belarus. The choice between the Piasts’ and the Jagiellonians’ foreign policy concepts for the III Republic of Poland raised controversies among the governmental circles and the political elites. The former concept implies aspiration for deepening European integration and Poland’s firmbasis in Europe, the latter perceives the country as a strong link of the European Union, able to exert influence over its Eastern neighbours in the particular values transfer process. While juxtaposing the two concepts, the representatives of the political elites of the III Republic of Poland prove thereby their incomprehension of the modern political processes that are taking place in Europe and all over the world as well as lack of professionalism commonly replaced by bare ideology. The discussion on the choice of directions and methods of foreign policy implementation often neither takes into account the dynamically changing international environment nor the real potential and capabilities of Poland.
Keywords: polityka wschodnia; Ukraina; Federacja Rosyjska; Unia Europejska; NATO; relacje polsko-ukraińskie; stosunki polsko-rosyjskie; Kościół katolicki; kościół prawosławny; dyplomacja publiczna; bezpieczeństwo; Katyń; polityka wschodnia RP